EU-Israel Relations, among the V4 – Analysis of Intelligence-sharing, Migration Crisis, Arms and Economic relations - Marton Seidner (European Scientific Journal, ESJ, 2022)
The relationship between the European Union (focus on the V4) and Israel will be examined in the light of intelligence and information sharing. To what extent are EU intelligence organizations working well, is there an efficient flow of information between different organizations? I would carry out an analysis of the current state of cooperation and look at possible breakthroughs that could lead to a forward-looking cooperation between the agencies. This could have an indirect effect on cooperation between the European Union and the countries covered by the Union's neighborhood policy in order to develop security policy processes. In addition to the operation of intelligence, I analyze the armaments indicators of the V4s and the political and economic relations of the V4s with the Mashrek region.